AAV-Mediated Overexpression of the CB1 Receptor in the mPFC of Adult Rats Alters Cognitive Flexibility, Social Behavior, and Emotional Reactivity - Klugmann, Matthias; Goepfrich, Anja; Friemel, Chris M.; Schneider, Miriam (Frontiers in Behavioral Neuroscience, 2011)
The endocannabinoid (ECB) system is strongly involved in the regulation of cognitive processing and emotional behavior and evidence indicates that ECB signaling might affect these behavioral abilities by modulations of prefrontal cortical functions. The aim of the present study was to examine the role of the CB1 receptor in the medial prefrontal cortex (mPFC) on cognitive flexibility and emotional behavior. Therefore, the CB1 receptor was overexpressed by adeno-associated virus (AAV) vector-mediated gene transfer specifically in the mPFC of adult Wistar rats. Animals were then tested in different anxiety-related paradigms for emotional reactivity (e.g. elevated plus maze (EPM), light/dark emergence test (EMT), social interaction) and the attentional set shift task (ASST) - an adaptation of the human Wisconsin card sorting test - for cognitive abilities and behavioral flexibility. A subtle increase in exploratory behavior was found in CB1 receptor overexpressing animals (CB1-R) compared to empty vector injected controls (Empty) in the EMT and EPM, although general locomotor activity did not differ between the groups. During social interaction testing, social contact behavior towards the unknown conspecific was found to be decreased, whereas social withdrawal was increased in CB1-R animals and they showed an inadequate increase in exploratory behavior compared to control animals. In the ASST, impaired reversal learning abilities were detected in CB1-R animals compared to controls, indicating reduced behavioral flexibility. In conclusion, upregulation of the CB1 receptor specifically in the rat mPFC induces alterations in emotional reactivity, leads to inadequate social behavior and impairs cognitive flexibility. These findings might be relevant for neuropsychiatric disorders, since higher cortical CB1 receptor expression levels as well as similar behavioral impairments as observed in the present study have been described in schizophrenic patients.